1998
DOI: 10.1364/ol.23.001010
|View full text |Cite
|
Sign up to set email alerts
|

16-µm infrared generation by difference-frequency mixing in diffusion-bonded-stacked GaAs

Abstract: Tunable 90-ps 15.6-17.6-microm coherent radiation was generated by means of difference-frequency mixing in diffusion-bonded-stacked GaAs. The sample consisted of 24 alternately rotated layers with a total length of 6 mm and with low optical loss to achieve third-order quasi-phase matching. The wavelength-tuning curve was close to the theoretical prediction, demonstrating that the bonding process maintained nonlinear optical phase matching over the entire interaction length. Maximum conversion efficiency of 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 5 publications
0
19
1
Order By: Relevance
“…This QPM problem was solved first by the stack of plates approach 2 and made practical with the addition of wafer bonding. 3,4 This approach proved successful and capable of generating crystals of large aperture, but remains limited, as it is a serial fabrication process. In addition, fabricating very short period gratings by these techniques is extremely challenging.…”
mentioning
confidence: 99%
“…This QPM problem was solved first by the stack of plates approach 2 and made practical with the addition of wafer bonding. 3,4 This approach proved successful and capable of generating crystals of large aperture, but remains limited, as it is a serial fabrication process. In addition, fabricating very short period gratings by these techniques is extremely challenging.…”
mentioning
confidence: 99%
“…Two-photon absorption is especially important for MIR devices which employ semiconductor crystals as gain media. For instance, AgGaS 2 , HgGa 2 S 4 should be pumped at wavelengths longer than 1.1 µm [68,69,79], for OP-GaAs, wavelengths above 1.55 µm should be used [51,80], while for ZnGeP 2 , pump wavelengths should be longer than 2 µm [71,81]. In oxide materials, including structured ferroelectrics, the fundamental bandgap is in the ultraviolet spectral region.…”
Section: Collinear Interactionmentioning
confidence: 99%
“…Zinc-blende semiconductor compounds, such as GaAs, are excellent candidates for nonlinear optical frequency conversion in the infrared by QPM, if periodic crystal domain inversions are incorporated in those otherwise optically isotropic materials. The effective nonlinear optical coefficient of GaAs is higher than ferroelectric materials, such as periodically-polled LiNbO 3 . GaAs is also attractive for its high thermal conductivity, high laser damage threshold, and transparency from 0.8 µm to 17 µm and in the very far infrared to terahertz.…”
Section: Introductionmentioning
confidence: 96%
“…Second harmonic generation (SHG) in a QPM GaAs was first demonstrated using a 10.6 µm laser in 1976. 2 Wavelength conversion by difference frequency generation (DFG) in QPM GaAs and AlGaAs was also realized for long-wavelength infrared (LWIR) 3 and short-wavelength infrared (SWIR), 4 respectively. Most recently, Vodopyanov et al demonstrated room temperature terahertz generation in QPM GaAs using femtosecond laser pulses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation